Islam dan Ekonomi, Islamisasi Ilmu Ekonomi - windari, windari; Ridwan, M; Tarigan, Azhari Akmal (Jurnal Ilmiah Ekonomi Islam, 2024)
Islam and Economy: Towards the Islamization of Economic Knowledge offers a profound understanding of Islam's contributions to forming a more inclusive and sustainable economic paradigm. The discussion on Islam and economics, as well as the movement towards the Islamization of economic knowledge, is essential to understand in the context of realizing the vision of justice and social welfare mandated by Islamic teachings. This research method is descriptive and analytical, focusing on the collection of secondary data from various relevant literature sources. The analysis employs qualitative methods by interpreting and summarizing information from various sources to draw conclusions. The results indicate that the understanding and application of Islamic economic principles are becoming increasingly relevant. Islam, as a comprehensive religion and way of life, offers a unique and sustainable perspective on economics that encompasses not only material aspects but also moral and spiritual dimensions. The Islamization of economic knowledge is an effort to develop an economic system that reflects Islamic values. This involves not just the application of Sharia law but also building a foundation for an economy that is fair, ethical, and sustainable. The process of Islamization occurs gradually, beginning with an in-depth study of the discipline of knowledge that is the subject of Islamization. This involves a thorough analysis of the worldview, philosophy, and underlying values of the discipline. The next step is to eliminate elements that do not align with Islamic teachings and integrate those that do.